POLA KEKERASAN DALAM KONFLIK SUMBER DAYA ALAM DI SUMATERA BARAT - Dewi Anggraini; Wewen Kusumi Rahayu; Syaifuddin Islami (Ensiklopedia of Journal, 2023)
Natural resource conflicts, especially mining conflicts, are often accompanied by violence committed by the State in collaboration with capital owners. Mining conflicts that lead to violence occur in Indonesia. From KPA data in 2022, there are at least 212 natural resource conflicts in 34 provinces throughout Indonesia with a land area of 1 million hectares. These conflicts involve at least 346,000 affected families. In West Sumatra alone from data released by LBH Padang in 2021, there are around 5,966 hectares of conflict land in several districts, such as West Pasaman, Agam and South Solok. The West Sumatra Civil Society Coalition (KMSS) also recorded that throughout 2018 there were 20 cases of natural resource conflicts on 80,637 hectares of land. Where the forest and land sector contributed the largest number with 8 cases fighting over 49,407 hectares of land, followed by the mining and energy sector with 5 cases with 29,840 hectares of land and finally the conflict of the infrastructure development sector with 7 cases on an area of 1,900 hectares. Two dominant cases that have captured public attention lately are gold mining conflicts in Nagari Simpang Tonang, Pasaman Regency. The conflict occurred between the people of Nagari Simpang Tonang, Duo Koto District, Pasaman Regency and PT. Inexco Jaya Makmur (IJM). Another case of conflict occurred between communities in Salingka Gunung Talang consisting of several nagari in conflict with PT. Hitay Daya Energi in geothermal energy exploration for power plants which also involves the local government of Solok Regency. In both cases, the conflict caused 59 people to experience intimidation and even 54 of them experienced physical violence, some even processed through legal channels